Modulation Role of Abscisic Acid (ABA) on Growth, Water Relations and Glycinebetaine Metabolism in Two Maize (Zea mays L.) Cultivars under Drought Stress - Zhang, Lixin (Molecular Diversity Preservation International (MDPI), 2012)
The role of plant hormone abscisic acid (ABA) in plants under drought stress (DS) is crucial in modulating physiological responses that eventually lead to adaptation to an unfavorable environment; however, the role of this hormone in modulation of glycinebetaine (GB) metabolism in maize particularly at the seedling stage is still poorly understood. Some hydroponic experiments were conducted to investigate the modulation role of ABA on plant growth, water relations and GB metabolism in the leaves of two maize cultivars, Zhengdan 958 (ZD958; drought tolerant), and Jundan 20 (JD20; drought sensitive), subjected to integrated root-zone drought stress (IR-DS) simulated by the addition of polyethylene glycol (PEG, 12% w/v, MW 6000). The IR-DS substantially resulted in increased betaine aldehyde dehydrogenase (BADH) activity and choline content which act as the key enzyme and initial substrate, respectively, in GB biosynthesis. Drought stress also induced accumulation of GB, whereas it caused reduction in leaf relative water content (RWC) and dry matter (DM) in both cultivars. The contents of ABA and GB increased in drought-stressed maize seedlings, but ABA accumulated prior to GB accumulation under the drought treatment. These responses were more predominant in ZD958 than those in JD20. Addition of exogenous ABA and fluridone (Flu) (ABA synthesis inhibitor) applied separately increased and decreased BADH activity, respectively. Abscisic acid application enhanced GB accumulation, leaf RWC and shoot DM production in both cultivars. However, of both maize cultivars, the drought sensitive maize cultivar (JD20) performed relatively better than the other maize cultivar ZD958 under both ABA and Flu application in view of all parameters appraised. It is, therefore, concluded that increase in both BADH activity and choline content possibly resulted in enhancement of GB accumulation under DS. The endogenous ABA was probably involved in the regulation of GB metabolism by regulating BADH activity, and resulting in modulation of water relations and plant growth under drought, especially in the drought sensitive maize cultivar JD20.